2005
DOI: 10.1529/biophysj.105.060020
|View full text |Cite
|
Sign up to set email alerts
|

Pathways and Timescales of Primary Charge Separation in the Photosystem II Reaction Center as Revealed by a Simultaneous Fit of Time-Resolved Fluorescence and Transient Absorption

Abstract: We model the dynamics of energy transfer and primary charge separation in isolated photosystem II (PSII) reaction centers. Different exciton models with specific site energies of the six core pigments and two peripheral chlorophylls (Chls) in combination with different charge transfer schemes have been compared using a simultaneous fit of the absorption, linear dichroism, circular dichroism, steady-state fluorescence, transient absorption upon different excitation wavelengths, and time-resolved fluorescence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(128 citation statements)
references
References 46 publications
6
122
0
Order By: Relevance
“…Or, alternatively, the 1,670-cm ÏȘ1 response may be due to Chl D1 (see above) and that at 1,681 cm ÏȘ1 may be due to H D1. We can compare this tentative assignment of the PC-P*͞P spectrum, which would indicate that the PC excited state is delocalized over P D1 , Chl D1 , and H D1 , with recent exciton calculations on the pigments in the PS2 RC: Novoderezhkin et al (46) reported the lowest exciton state at Ï·680 nm to be delocalized mainly over P D1 and Chl D1 , and over H D1 and Chl ZD1 , i.e., the pigments on the active branch of the RC, and charge separation from this state to be very fast, which is in good agreement with our assignments. However, the prediction of the calculations of Raszewski et al (47) is that the lowest exciton states are localized on Chl D1 and H D2 , and the interpretation of P Ï© ͞P spectra of mutants of PS2 cores is that Chl D1 , Chl D2 , H D1 , and H D2 all absorb between 680 and 684 nm but that P D1 and P D2 absorb near 673 and 675 nm, respectively (9,22).…”
Section: Population Of H D1mentioning
confidence: 81%
“…Or, alternatively, the 1,670-cm ÏȘ1 response may be due to Chl D1 (see above) and that at 1,681 cm ÏȘ1 may be due to H D1. We can compare this tentative assignment of the PC-P*͞P spectrum, which would indicate that the PC excited state is delocalized over P D1 , Chl D1 , and H D1 , with recent exciton calculations on the pigments in the PS2 RC: Novoderezhkin et al (46) reported the lowest exciton state at Ï·680 nm to be delocalized mainly over P D1 and Chl D1 , and over H D1 and Chl ZD1 , i.e., the pigments on the active branch of the RC, and charge separation from this state to be very fast, which is in good agreement with our assignments. However, the prediction of the calculations of Raszewski et al (47) is that the lowest exciton states are localized on Chl D1 and H D2 , and the interpretation of P Ï© ͞P spectra of mutants of PS2 cores is that Chl D1 , Chl D2 , H D1 , and H D2 all absorb between 680 and 684 nm but that P D1 and P D2 absorb near 673 and 675 nm, respectively (9,22).…”
Section: Population Of H D1mentioning
confidence: 81%
“…-formation, present in the Q x and anion bands, was predicted by the model (19,40) via the (P D1 P D2 Chl D1 Phe D1 )* f…”
Section: Discussionmentioning
confidence: 99%
“…The nonlinear spectral responses can also be expressed in terms of the line-broadening functions (Eq. 3.4), as shown for pump-probe spectra [29,[38][39][40][41][42], Stark spectra [28], photon echoes [36], and 2D echoes [43].…”
Section: Exciton-phonon Coupling and Spectral Line Shapesmentioning
confidence: 80%
“…That model was later replaced by more realistic models based on modified Redfield theory. These models employed the site energies extracted from a simultaneous evolutionarybased fit of linear spectra (OD, CD, LD, and FL) over a wide temperature range [41] and nonlinear spectra (time-resolved OD and FL at room temperature) [39]. In a later work, a CT state, which was strongly mixed with the exciton states, was included in the excitonic manifold [28].…”
Section: The Model: Simultaneous Fit Of Linear and Nonlinear Spectramentioning
confidence: 99%